Analisis Kepribadian Tokoh Utama dalam Film Adaptasi “Toba Dreams” Melalui Pendekatan Psikologi Sastra (Sigmund Freud) - Nainggolan, Debora Putriani Br; Manalu, Gresia Krisanta; Tobing, Jelita Teresia; Marbun, Rosliana; Manihuruk, Sonia; Amalia, Nadra (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study analyzes the personality of the main character in the film Toba Dreams using Sigmund Freud's literary psychology approach. The main focus of the study is the character Ronggur, who experiences inner conflict between his free will and family values. The method used is descriptive qualitative with observation and documentation techniques. The results show the dominance of id in Ronggur, which often clashes with his father's moral values as a representation of superego. This analysis shows that personality conflict can be the main key in understanding the dynamics of characters in movies